"Ready to take on the world": Experiences and understandings of independence after attending residential immersive life skills programs for youth with physical disabilities. (17th February 2018) - McPherson, Amy C.; Rudzik, Alanna; Kingsnorth, Shauna; King, Gillian; Gorter, Jan Willem; Morrison, Andrea
ABSTRACT: Statement of Purpose : Life skills programs aim to equip youth with physical disabilities with the foundational skills required for adulthood. This study explored the perceived impact of residential immersive life skills (RILS) programs on the lives of participants. Methods : Qualitative interviews were conducted with alumni of three RILS programs. Data were thematically analyzed using a phenomenological approach. Results : Themes identified from fourteen interviews were: (1) enhancing higher-order skills; (2) new notions of independence; and (3) identity change, empowerment, and advocacy. Opportunities to learn and practise a variety of skills in a structured, facilitative environment led to increased competence and motivation to engage in independent activities. Engaging with peers undergoing similar experiences also helped some youth integrate disability into their identity. Conclusions : Providing youth with physical disabilities opportunities to engage with others sharing similar experiences and challenges is essential. The study contributes toward the development of evidence-based best practices for life skills programs.